La norma violata. Metafore del corpo in medicina e nella prosa kafkiana - Alessandra Zurolo (Studia austriaca)
The concept of body is closely related to that of illness and its various manifestations, a connection that can be observed from a range of perspectives. The present study draws upon the metaphors of the body found in selected German medical textbooks and aims to compare the image of the healthy and the pathological body in the tradition of German-language medical education with how it is presented in selected writings by the author who perhaps most emblematically – within the sphere of German literature – provided examples of the theme in question: Franz Kafka. The politicisation of the body, its presentation as a space of definition, refusal, violation, renegotiation of the norm (which recalls Foucault’s thought) and the subsequent definition and manifestation of the pathological are indeed revealed in Franz Kafka’s work in an exemplary manner. The study will explore the differences and points of contact between the medical notion of the body and its artistic-literary representation, starting from the metaphor of illness as a violation of the norm, as found in medical textbooks and selected novels. The analysis thus offers a contribution to the definition of the body in both the medical and literary spheres, and, more generally, to the description of the different manifestations, functions and relationships of the use of metaphor for the same concept in different fields of knowledge.